Effect of a post-weaning restricted nutrition on the initiation of puberty, plasma leptin and the reproductive performances of early bred Merino ewe-lambs - Blanc F.; Fabre D.; Bocquier F.; Canepa S.; Delavaud C.; Caraty A.; Chilliard Y.; Debus N. (Advanced nutrition and feeding strategies to improve sheep and goat, 2007)
The study assessed the effect of the nutrition level from weaning to mating on the onset of puberty and the reproductive performances of early mated (9-10 months old) ewe-lambs. Three month-old ewe-lambs were allocated to one of 3 treatments: High group (H, n=10) was fed ad libitum with a ration of dried beet pulp (50%), dehydrated alfafa meal (40%) and straw pellets (10%). Medium (M, n=10) and Low (L, n=10) groups were first underfed (respectively at 70% and 40% of the amount of feeds offered to group H) from 13 to 38 weeks of age and then fed ad libitum until 46th week of age. Three weeks after the beginning of the refeeding period oestrous behaviour was checked twice a day and ewe-lambs in oestrous were mated. Blood samples were collected twice a week to monitor plasma progesterone (P4) and leptin concentrations. Individual food intake, weight and body condition score (BCS) were respectively measured every day, every week and every 2 weeks. All animals except one in group H, reached puberty (P4 >1 ng/ml) before the end of the study. Age at puberty did not differ between groups H (32.9±2.0 weeks) and M (32.2±2.0 weeks) but was delayed for group L (38.6±3.4 weeks). Only four ewe-lambs in group L reached puberty before the refeeding period at a mean age of 35.3 weeks. Weights (H: 43.5±4.3, M: 36.8±3.1, L: 32.0±3.4 kg) and BCS (H: 3.2±0.2, M: 2.9±0.2, L: 2.1±0.2) at puberty decreased with the undernutrition level. Leptinemia at puberty was higher in group H (11.6±5.5 ng/ml) than in groups M and L (5.6±1.3 and 4.6±1.6 ng/ml, respectively). Oestrous manifestation rates (respectively 90, 70 and 40%) decreased with the feeding restriction, whereas productivity reached 60, 60 and 30%. To conclude, only L treatment delayed the onset of puberty and affected the reproductive performances. Neither weight, nor BCS or leptin per se appeared to be primary cues for puberty but could play a permissive role.
11. Seminar of the FAO-CIHEAM Sub-Network on Sheep and Goat Nutrition, 2005/09/08-10, Catania (Italy)